Natural production of organohalogen compounds - Gribble, Gordon W., ....- (Berlin : Springer, 2003)
Samenvatting:This book summarizes the state-of-the-art knowledge on naturallyoccurring organohalogens, of which more than 3700 are documented. Thechapters cover all aspects of this field, including the structuraldiversity and sources of organohalogens, the mechanisms for theirformation and biodegradation, the clinical use of dichloroacetate, andthe synthesis of the powerful anticancer chlorine-containingcryptophycin. Both biogenic and abiogenic sources of organohalogens aretreated, the latter of which include volcanic emissions and abiogenicformation in soil. Halogenation in humans, fungi, and in the ocean arecovered in separate chapters. Sources and biosynthesis of the relativelyrare natural organofluorines are also discussed in this volume. By betterunderstanding of the role nature plays in the area of organohalogens, wecan more intelligently regulate the production, use, and disposal ofman-made organohalogen compounds.
Keywords: Organische halogeenverbindingen